Pipeline wall thickness assessment of various material grades and water depths using American and norwegian standards - Mohr Azril Ahamad,; Haniff Abdul Rahman,; Siti Aminah Osman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Two standards that are widely used by many countries in designing offshore gas transmission pipelines are American Standard – ASME B31.8, Gas Transmission and Distribution Piping Systems and Norwegian Standard – DNVGL-ST-F101, Submarine Pipeline System. A thorough understanding of these standards is vital in determining optimal pipeline design to ensure pipeline integrity for safe and sustainable operations, as well as striving for economic efficiency. This study aims to evaluate the wall thickness required for pipeline designs using American and Norwegian pipeline standards under different steel grades and water depth conditions. Pipeline costs are then compared for both standards at each water depth condition for commercial evaluation. Through this, the optimal pipeline standard for wall thickness design can be determined. Mathcad software was used for data analysis in accordance with the standards mentioned and all design requirements including pressure containment, collapse, and propagation buckling. Ultimately, the American Standards was able to provide a total cost that was 2.5% lower than the Norwegian Standard for a pipeline project with a combination of shallow, medium, and deepwater depths along its route. However, a combination of Norwegian Standards for medium and deepwater depths and American Standard for shallow water depth can further reduce total costs to 2% compared to only using the American Standard. This study highlights the importance of considering several design standards for a pipeline project instead of strictly adhering to a single standard for better technical and commercial benefit.